FAKTOR-FAKTOR YANG MEMPENGARUHI TERJADINYA STUNTING PADA BALITA USIA 24-59 BULAN - Lisa Tanzil; Hafriani Hafriani (Program Studi Kebidanan Fakultas Kedokteran Universitas Malahayati, 2021)
ABSTRACT FACTORS AFFECTING STUNTING IN CHILDREN AGE 24-59 MONTHS Background: Stunting is a description of chronic malnutrition in the period of growth and development since early life. Many factors can cause stunting in children under five, such as the characteristics of toddlers and socioeconomic characteristics. The prevalence of stunting in Indonesia is the fifth largest in the world. Basic health research data (Riskesdas) in 2013 showed the prevalence of stunting in the national scope of 37.2 percent, consisting of a stunting prevalence of 18.0 percent and very short prevalence of 19.2 percent. Stunting is considered a serious public health problem when the prevalence of stunting is in the 30-39 percent range. Purpose: This study aims to determine the factors that cause stunting in toddlers aged 24-59 monthsMethods: This study was an analytic observational study with a case control conducted in the working area of the Simpang Ulim Public Health Center, East Aceh. Samples were taken as many as 20 toddlers as a case group and 20 toddlers as a control group with a purposive sampling technique. Data analysis used the chi square test and used cross tabulation to analyze the closeness of the relationship between two variables by looking at the Odds Ratio (OR) value.Results: The study showed that energy adequacy (OR = 9,333; CI = 2,180-39,962), protein adequacy (OR = 7000; CI = 1,739-28,174), maternal knowledge (OR = 7000; CI = 1.739-28174), maternal education (OR = 22,667; CI = 4,374-117,468), family income (OR = 13,222; CI = 2,790-62,670) was a risk factor for stunting, while other factors in this study were low birth weight (LBW) (OR = 1,588; CI (0.236-10.704), history of breastfeeding (OR = 0.474; CI (0.39-5.688) and maternal occupation (OR = 1.238; CI = 0.343-4.64) were not risk factors for stunting.Conclusion: Lack of energy and protein intake, less knowledge of mothers, low education of mothers and low family income are risk factors for stunting in children aged 24-59 months.Suggestion It is hoped that the Puskesmas and other related sectors can increase maternal knowledge about the nutritional needs of toddlers through nutritional counseling activities which include education on nutritional adequacy rates for children under five according to age, how to properly process food, and provide financial assistance for underprivileged families. It is hoped that mothers of toddlers can actively participate in posyandu activities so that they are more often exposed to nutritional fulfillment information for toddlers. Keywords: Stunting, Risk Factor, Toddler, Simpang Ulim ABSTRAK Latar Belakang: Stunting merupakan penggambaran dari status gizi kurang yang bersifat kronik pada masa pertumbuhan dan perkembangan sejak awal kehidupan. Banyak factor yang dapat menyebabkan terjadinya stunting pada balita seperti karakteristik balita maupun social ekonomi. Prevalensi stunting di Indonesia menempati peringkat kelima terbesar di dunia. Data Riset kesehatan dasar (Riskesdas) tahun 2013 menunjukkan prevalensi stunting dalam lingkup nasional sebesar 37,2 persen, terdiri dari prevalensi pendek sebesar 18,0 persen dan sangat pendek sebesar 19,2 persen. Stunting dianggap sebagai masalah kesehatan masyarakat yang berat bila prevalensi stunting berada pada rentang 30-39 persen.Tujuan: Penelitian ini bertujuan untuk mengetahui factor-faktor yang menyebabkan terjadinya stunting pada balita usia 24-59 bulan.Metode: Penelitian ini merupakan penelitian observasional analitik dengan kasus kontrol yang dilakukan di wilayah kerja UPTD Puskesmas Simpang Ulim, Aceh Timur. Sampel yang diambil sebanyak 20 balita sebagai kelompok kasus dan 20 balita sebagai kelompok kontrol dengan teknik purposive sampling. Analisis data menggunakan uji chi square serta menggunakan tabulasi silang untuk menganalisis keeratan hubungan antara dua variabel dengan melihat nilai Odds Ratio (OR).Hasil: Pada penelitian menunjukkan bahwa kecukupan energy (OR=9.333; CI=2.180-39.962), kecukupan protein (OR=7000; CI=1.739-28.174), pengetahuan ibu (OR=7000; CI=1.739-28174), pendidikan ibu (OR=22.667; CI=4.374-117.468), pendapatan keluarga (OR=13.222; CI=2.790-62.670) merupakan factor resiko terjadinya stunting, sedangkan factor lainnya dalam penelitian ini yaitu berat badan lahir rendah (BBLR) (OR=1.588; CI (0.236-10.704), Riwayat ASI (OR=0.474; CI (0.39-5.688) dan pekerjaan ibu (OR=1.238; CI=0.343-4.64) bukan merupakan factor resiko terjadinya stunting.Kesimpulan: Asupan energi dan protein yang kurang, pengetahuan ibu yang kurang, pendidikan ibu yang rendah serta pendapatan keluarga yang rendah merupakan fakor resiko terjadinya stunting pada balita usia 24-59 bulan.Saran Bagi pihak Puskesmas dan lintas sektoral yang terkait diharapkan dapat meningkatkan pengetahuan ibu tentang kebutuhan nutrisi pada balita melalui kegiatan penyuluhan gizi yang meliputi edukasi mengenai angka kecukupan gizi pada balita sesuai umur, cara mengolah makanan yang benar, serta memberikan bantuan finansial bagi keluarga yang tidak mampu. Bagi ibu balita diharapkan dapat aktif mengikuti kegiatan posyandu supaya lebih sering terpapar dengan informasi pemenuhan nutrisi pada balita. Kata kunci : Stunting, Factor Resiko, Balita, Simpang Ulim